Hubungan Antara Psychological Capital dengan Subjective Career Success pada Karyawan Generasi Milenial - Puji Tania; Maria Catalina Rosari (MANASA, 2021)
This study aims to determine the relationship between psychological capital and subjective career success in millennial generation employees. This study involved 129 millennial generation employees. The type of design of this research is correlational. The measuring instrument used of two questionnare, namely psychological capital questionnaire (PCQ) and subjective career success inventory (SCSI). Data processing with Pearson correlation. The results showed that there is a significant positive relationship between psychological capital and subjective career success in millennial generation employees (r(127)=0.551, sig (2-tailed)=0.000). Thus, the higher the psychological capital owned by millennial generation employees, the higher the subjective career success of millennial employees. Penelitian ini bertujuan mengetahui hubungan antara psychological capital dengan subjective career success pada karyawan generasi milenial. Penelitian ini melibatkan 129 karyawan generasi milenial. Subjek dipilih menggunakan teknik convenience sampling. Jenis desain dari penelitian ini adalah korelasional. Alat ukur yang digunakan terdiri dari dua alat ukur, yaitu psychological capital questionnaire (PCQ) dan subjective career success inventory (SCSI). Pengolahan data dengan uji korelasi pearson. Hasil penelitian menunjukkan bahwa terdapat hubungan positif yang signifikan antara psychological capital dengan subjective career success pada karyawan generasi milenial (r(127)=0.551, sig (2-tailed)=0.000). Dengan demikian, semakin tinggi psychological capital yang dimiliki oleh karyawan generasi milenial maka semakin tinggi subjective career success karyawan generasi milenial.